With amusement for all : a history of American popular culture since 1830 - Ashby, LeRoy (Lexington : University Press of Kentucky, 2006)
"With Amusement for All contextualizes what Americans have done for fun since 1830, showing the reciprocal nature of the relationships among social, political, economic, and cultural forces and the ways in which the entertainment world has reflected, changed, or reinforced the values of American society."--Jacket.
Prologue : popular culture on the brink -- Blackface, Barnum, and newspaper ballyhoo -- Taming rough amusements, 1840s-1860s -- Building an entertainment industry -- The billion-dollar smile : from burlesque to vaudeville and amusement parks -- The leisure problem at the turn of the century -- Popular culture and middle-class respectability in the early twentieth century -- Battling the Great Depression -- Building a wartime consensus in the 1940s and 1950s -- Counterpoints to consensus -- Popular culture and 1960s ferment -- Up for grabs : leaving the 1960s -- A pop culture society -- Epilogue : pop culture in a post-9/11 world.
Includes bibliographical references (pages 587-612) and index.
Keywords: Popular culture -- United States -- History; Amusements -- United States -- History; United States -- Civilization; United States -- Social conditions; Culture populaire -- Histoire; Spectacles et divertissements -- Histoire; Civilisation; Conditions sociales; Amusements; Civilization; Popular culture; Social conditions; United States; Populaire cultuur; Massamedia; Amusement; Massenkultur; USA; Volkskultur; USA; Geschichte 1830-2005.; History